Enhancing 3D-Printed Bra Cup Design Through Lattice Structure Optimisation (Journal of Fiber Bioengineering and Informatics, 2025)
With the development of 3D printing technology, its application in the apparel industry, especially in bracup design, has drawn attention. Previous studies have explored the use of 3D printing for underwearcustomisation. Yet, issues such as poor flexibility, heavy weight, excessive material consumption, andlow comfort of printed materials remain, limiting the wide application of 3D-printed bra cups. There isa research gap in effectively optimising the structural design of 3D-printed bra cups to overcome thesedrawbacks. This paper aims to address this gap by investigating the use of lattice structures in designing3D-printed bra cups and analysing how rod diameter and material hardness affect the elastic modulusof the lattice-based cup designs. Through a series of experiments, it is found that both parameterssignificantly influence the modulus, with material hardness being more crucial. By using the RESIONEF80 material with a 1 mm rod diameter for lattice infill, the volume of the 3D printed cup is reduced by45.16%, porosity is enhanced, and ventilation and comfort are greatly improved.
Keywords: 3D Printing; Lattice Structure; Bra Cup; Comfort.